Grading quality of total mesorectal excision specimen by surgeons - Maharjan, Dhiresh Kumar; Thapa, Prabin Bikram (Journal of Kathmandu Medical College, 2018)
Background: Total mesorectal excision has been gold standard since 1978. But standardization of surgery with quality assurance of total mesorectal excision specimen has been a challenging issue in developing countries. However, quality of macroscopic total mesorectal excision can be graded immediately by operating surgeon before specimen has been fixed in formalin and photographic documentation of gross specimen by surgeons is possible and practical.Objective: To grade macroscopic total mesorectal excision specimen by surgeon and document it photographically and compare it with reporting received from pathologist. Methods: A prospective observational study conducted from Jan 2014 to Jan 2016 at Department of Surgery, Kathmandu Medical College Teaching Hospital, Kathmandu, Nepal. All consecutive patients with rectal cancer (upper/middle and lower) without distant metastasis were included. Immediate after surgery, macroscopic specimen of TME were graded by operating surgeon and photo-documentation with one anterior, one posterior and two right and left lateral views of total mesorectal excision photos were taken and documented with printed form along with operative notes.Results: There were 40 patients with rectal cancer who underwent surgery during this period. Among those patients, the median age was 25 years of which 30% were females. Twenty-four patients underwent low anterior resection whereas thirteen had ultralow anterior resection and three had abdominal perineal resection. All patients had photo documentation. Complete mesorectal excision was seen in 36 patients and four patients had near complete total mesorectal excision when graded by surgeons. However, pathologist reported six (16.6%) patients having near complete mesorectum among those which had been graded as complete by surgeons.Conclusion: Grading of macroscopic total mesorectal excision specimen by surgeon is feasible and with use of photographic documentation, it can help to assess the quality of surgeons work and can be a good tool for feedback for surgeons to improve.